2008
DOI: 10.1634/stemcells.2008-0034
|View full text |Cite
|
Sign up to set email alerts
|

IFATS Collection: In Vivo Therapeutic Potential of Human Adipose Tissue Mesenchymal Stem Cells After Transplantation into Mice with Liver Injury

Abstract: ␣ (IL-1R␣), IL-6, IL-8, granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), monocyte chemotactic protein 1, nerve growth factor, and hepatocyte growth factor in a volume higher than both BMMSCs and NHDFs. Thus, our findings suggest that ATMSCs may account for their broad therapeutic efficacy in animal models of liver diseases and in the clinical settings for liver disease treatment. STEM CELLS 2008;26: 2705-2712 Disclosure of potential conflicts of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
251
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(263 citation statements)
references
References 57 publications
5
251
0
7
Order By: Relevance
“…There are various possible routes of administration of MSCs, including intravenous (Banas et al, 2008), intraarterial (Lu et al, 2001) or intracerebral (Chen et al, 2000) routes. Of these routes, intravenous administration is a convenient strategy if the cells are delivered to the injury site after systemic circulation through the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various possible routes of administration of MSCs, including intravenous (Banas et al, 2008), intraarterial (Lu et al, 2001) or intracerebral (Chen et al, 2000) routes. Of these routes, intravenous administration is a convenient strategy if the cells are delivered to the injury site after systemic circulation through the lung.…”
Section: Discussionmentioning
confidence: 99%
“…(Mizuno, 2010). Local or systemic administration of AdMSCs was reported to induce repair of myocardial infarction (Cai et al, 2009), liver injury (Banas et al, 2008), hypoxia-ischemia-induced brain damage (Wei et al, 2009), allergic rhinitis (Cho et al, 2009) and muscular dystrophy (Bacou et al, 2004). One of the more interesting characteristics of MSCs is their ability to migrate to areas of tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia, uric acid, glutamic-pyruvic transaminase, and glutamic-oxaloacetic transaminase concentrations returned to a nearly normal level after AT-MSC trans- There is no change in size with DDLT, whereas graft enlargement is observed with LDLT. Functional recovery follows volume recovery; therefore, there should be some critical period with LDLT after operation IL-8, granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), monocyte chemotactic protein 1, nerve growth factor, and hepatocyte growth factor, suggesting that AT-MSCs account for broad therapeutic effi cacy in animal models of liver diseases and in the clinical settings of liver disease treatment [ 3 ].…”
Section: Characteristicsmentioning
confidence: 99%
“…14 Several animal and clinical trials have demonstrated that MSCs have the potential to reverse the fibrotic process by inhibiting collagen deposition and transforming growth factor-b1 production and by their capacity to differentiate into hepatocytes. [15][16][17] The antifibrotic mechanism of MSC transplantation can be mainly attributed to the high levels of matrix metalloproteinase-9 expressed by MSCs, which may directly degrade the extracellular matrix 18 and indirectly regulate hepatic stellate cells to secrete cytokines. In addition, MSC-derived IL-10 and TNF-a can also inhibit hepatic stellate cell regeneration and matrix synthesis.…”
Section: Therapeutic Mechanism Of Msc Transplantationmentioning
confidence: 99%
“…In animal studies, the quantity of transplanted stem cells is usually about 10 6 -10 7 . In two of the clinical studies mentioned above, four patients with decompensated cirrhosis 15 and eight cirrhosis patients with ESLD received 3.2310 7 and 3-5310 7 autologous BM-MSCs, respectively, through the peripheral or portal vein. 21 In both trials, all the patients tolerated the transplantation well during and until the end of the follow-up period.…”
Section: Quality Parameters For the Application Of Mscsmentioning
confidence: 99%